MENGEMBANGKAN KEMAMPUAN MENULIS AWAL ANAK USIA DINI DENGAN MEDIA PUZZLE - Anita Bella Prastiyanti; Ahmad Fachrurrazi (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
Now the initial writing activities at school need to be developed and modified again to attract early childhood interest in early writing activities through media puzzle. Early writing skills have a very important role in literacy recognition. The purpose of this study is to find out and describe more deeply and comprehensively about the effect of puzzle media on the early writing ability of group B TK Agripina Surabaya. The method used in this study is a quantitative research method using the One Group Pretest - Postest design. The sample used was all students of Group B TK Agripina with a total of 20. Data were collected from the results of observations of performance tests, with instrument performance observation sheets. Data analysis techniques using the t test formula. The results showed that the calculated value t = 8.40 is greater than the value of t table (1.72913) at the 0.05 significance level and (2.53948) at the 0.01 significance level, then the null hypothesis was rejected so that the working hypothesis was accepted. This shows the Working Hypothesis proved to be very significant. Thus it can be stated that